Mental health in children of parents being treated by specialised psychiatric services. Issue 8 (December 2022) - Nordh, Emme-Lina W.; Priebe, Gisela; Grip, Karin; Afzelius, Maria; Axberg, Ulf
Background: One in ten children have a parent diagnosed with a mental illness by specialised psychiatric services. Severe parental mental illness is a well-established risk factor for children's mental health problems, making the identification and support of these children a public health concern. This study investigated the mental health and family context of children of parents diagnosed with depression, anxiety, or bipolar disorder in this clinical setting. Methods: Parental reports on 87 children aged 8–17 years were analysed. The children's mental health was compared with that of a Swedish population-based sample. Multiple linear regression was used to investigate associations between child mental health and child gender, child age, parent symptoms and social status, family functioning, and perceived parental control. Furthermore, a cumulative risk index explored the effect of multiple risk factors on child mental health. Results: The children reportedly had significantly more mental health problems than did the population-based sample and about one-third had scores above the clinical cut-off. A significant multiple linear regression explained 49% of the variance in child mental health, with lower perceived parental control and younger child age being associated with more child mental health problems. With more reported risk factors, children reportedly had more mental health problems. Conclusions: The results underline the importance of identifying a patient's children and assessing multiple relevant risk factors in the child's life. Furthermore, the results indicate that the needs of younger children and of patients in their parenting role are important to address.